Strategi pembelajaran Abad 21 bagi guru-guru SMK Kartika XX-1 Makassar - Hasanah Hasanah; Nasir Malik (Seminar Nasional Pengabdian Kepada Masyarakat, 2019)
The partner of this Community Partnership Program (PKM) are Vocational School Teachers Kartika XX-1 Makassar. The problem is: (1) lack of partner understanding of 21st century learning, (2) Lack of partner knowledge planning integrated learning scenarios with 21st century skills and the values of the Industrial Revolution 4.0, and (3) lack of partner knowledge and skills in developing an Implementation Plan Learning (RPP). The world of work demands a change in competence, and schools must be able to prepare students to enter the 21st century. Activities carried out are: (a) Train partners to understand the concepts of 21st century learning and Industrial Revolution 4.0, (b) Train partners to design 21st Century Learning scenarios, (c) Train partners to compile 21st Century skills-based lesson plans. The method of conducting exercises is the method of lectures, discussions and questions and answers used to explain 21st century skills in the Industrial Revolution Era 4.0, and how to integrate the values of the industrial revolution 4.0 in the learning scenario so that 21st Century skills can achieve. While the method of practice, demonstration, discussion and question and answer are carried out to prepare Scenarios and Learning Implementation Plans. The results achieved are: (1) partners are able to understand the characteristics of 21st century learning, (b) partners are able to compile 21st century learning scenarios, and (c) partners are able to integrate the values of the Industrial Revolution 4.0 and 21st Century Skills in the RPP.